Hubungan Paparan Suara Bising dari Sound Horeg dengan Kejadian Vertigo pada Masyarakat di Kota/Kabupaten Malang - Vincentia Maria Iriane; Yuswanto Setyawan (Jurnal Ilmiah Kesehatan, 2026)
Noise exposure from sound horeg is an environmental factor that may affect hearing and body balance. This study aimed to analyze the relationship between sound horeg noise exposure and the incidence of vertigo among residents in Malang Regency. This research employed an analytical observational design with a cross-sectional approach involving 316 respondents living near sound horeg activity areas. Data were collected using questionnaires and a sound level meter to measure noise intensity, then analyzed using the Chi-Square test. The results showed a significant relationship between noise levels and the incidence of vertigo (p < 0.05), indicating that higher noise intensity increases the risk of vertigo occurrence. It was concluded that sound horeg noise exposure can trigger vestibular system disturbances that affect body balance. The study recommends stricter regulation of noise levels and increased public awareness of the health impacts of loud sound exposure. Keywords: noise exposure, sound horeg, vertigo, vestibular system, public health